Matching Abilities to Careers for Others and Self: Do Gender Stereotypes Matter to Students in Advanced Math and Science Classes? - Barth, Joan M.; Kim, Hwaheun; Eno, Cassie A.; Guadagno, Rosanna E. (Sex Roles, 2018)
Interest in STEM (science, technology, engineering, and mathematics) careers falls off more quickly for young women than for young men over adolescence, and gender stereotypes may be partially to blame. Adolescents typically become more stereotypical in their career interests over time, yet they seem to become more flexible in applying stereotypes to others. Models of career interest propose that career decisions result from the alignment of self-perceived abilities with occupation-required skills and that gender stereotypes may influence this process. To investigate the discrepancy between applying stereotypes to self and others, we examined if these models can be applied to perceptions of others. Focusing on students from fifth grade through college enrolled in advanced STEM courses, we investigated how STEM occupational stereotypes, abilities, and efficacy affect expectations for others’ and own career interests. U.S. participants (n = 526) read vignettes describing a hypothetical male or female student who was talented in math/science or language arts/social studies and then rated the student’s interest in occupations requiring some of those academic skills. Participants’ self-efficacy, interest, and stereotypes for STEM occupations were also assessed. Findings suggest that ability beliefs, whether for oneself or another, are powerful predictors of occupational interest, and gender stereotypes play a secondary role. College students were more stereotypical in their ratings of others, but they did not manifest gender differences in their own STEM self-efficacy and occupational interests. Experiences in specialized STEM courses may explain why stereotypes are applied differentially to the self and others.